Biomedical Cost Analysis of Tuberculosis Morbidity in Inpatients at dr. Soeselo Slawi Hospital, 2022 - fahamsya, arifina; Vandani, Chiara Dhinta; Nurhidayati, Lailiana Garna (Yayasan Siti Widhatul Faeha, 2025)
Tuberculosis is one of the deadly infectious diseases worldwide. It is caused by Mycobacterium tuberculosis infection. The cases of tuberculosis in 2022 were reported to be 824,000 with an annual death toll of 93,000. Tuberculosis is a disease caused by long-term treatment and falls under the ICD-10 code 16.2 for national health insurance coverage. The aim of this research is to determine the cost of illness due to tuberculosis from a health perspective and to determine the variables associated with the cost of illness due to tuberculosis at RSUD dr. Soeselo Slawi in 2022. This research method uses observational with a cross sectional research design on 82 patient data, descriptive analysis methods to determine cost estimates and statistical methods to determine the factors that influence the total cost of illness for tuberculosis patients. Based on the research, it shows that the cost of service is the highest cost component compared to other cost components. The average cost of supporting examinations is Rp. 753,827.00; service fee of Rp. 2,133,809.00; and pharmacy costs Rp. 1,873,449.00. The average cost of tuberculosis illness from a healthcare perspective is Rp. 4,761,085.00. The largest component of the illness costs is the service cost. The variables significantly associated with a Sig. (2-tailed) value ˂ 0.05 are the ward class, length of stay, diagnostic test costs, service costs, and pharmacy costs with respect to the total illness costs.